KARAKTERISTIK ORGANOLEPTIS SILASE RUMPUT GAJAH (Pennisetum purpureum) AKIBAT PENAMBAHAN KULTUR MIKROBIA CAMPURAN - Surono Surono (JURNAL LITBANG PROVINSI JAWA TENGAH, 2003)
Research was carried out to determine the effect of mixed-microbe culture (MMC) addition on organoleptics characteristic of Napier grass iPennisetum purpureumv silage. Contribution of the research was to inform alternative technology in ensiling with MMC addition. Research was conducted in Feed Science Laboratory, Animal Nutrition and Feed Science Department, Faculty of Animal Husbandry of Diponegoro University, Semarang. Napier grass was ensiled with the level of MMC addition as followed : TO= Napier grass+ 2,5% molasses+ 0% MMC Tl = Napier grass+ 2,5% molasses+ 2,5% MMC T2 = Napier grass + 2,5% molasses + 5% MMC T3 = Napier grass+ 2,5% molasses+ 7,5% MMC T4 = Napier grass+ 2,5% molasses+ 10% MMC Every treatment had 3 (three) replications. Collecting data (score) of organolepticscharateristic was done using panel test with 20 (twenty) panelis. Collected data analized using simple statistics. Result of the research showed that organoleptics caharteristic of experimental silage getting better along with the increasing level of MMC addition